Comparison between traditional resistance training and whole-body electrical Stimulation in improving muscular strength - Raja Nurul Jannat Raja Hussain (Tanjong Malim, 2021)
Comparison between traditional resistance training and whole-body electrical Stimulation in improving muscular strength by Raja Nurul Jannat Raja Hussain